Antiphase boundaries, magnetic domains, and magnetic vortices in Ni–Mn–Ga single crystals. (1st February 2020) - Vronka, Marek; Straka, Ladislav; De Graef, Marc; Heczko, Oleg
Abstract: The interplay between antiphase boundaries (APBs), magnetic domain structure and functional properties was investigated in the martensitic state of Ni–Mn–Ga single crystals which showed magnetically induced martensite reorientation (MIR) with 6% strain. The APB density was controlled by different heat treatments. The APBs and magnetic domains were observed by Lorentz transmission electron microscopy (LTEM). Slow cooling at ~1 K/min resulted in a low density (<1/µm), air quenching in a medium density (≈8/µm), and water quenching in a high density (≈15/µm) of APBs. Abundant pinning of domain walls on APBs was observed, which resulted in close correspondence between the magnetic domain walls and antiphase boundaries (APBs), magnetic domain memory, and finer domain patterns for the high APB density. For low APB density, a labyrinth domain structure was established between domain walls pinned on APBs. For low and medium density of APBs the magnetization was oriented mostly parallel to the out-of-plane easy magnetization axis. For high APB density the magnetization switched to the in-plane orientation, indicating that the effective magnetic anisotropy decreased and became lower than the stray field energy. In addition, magnetic vortices appeared. The novel functionalities based on a combination of MIR and interactions of the magnetic structure with APBs are feasible since the MIR was observed even for the highest density of APBs. Graphical abstract: Image, graphical abstract